Information Use Pattern by Sericulture Scientists: A Case Study of Karnataka State Sericulture Research and Development Institute Library, Bangalore - Biradar, R. S.; SampathKumar, B. T.; Anil Kumar, M. (Journal of Information and Knowledge, 2014)
Study attempted to identify the usefulness of 1ibrary collection and information use pattern by sericulture scientists. Result shows reports (52%). conference papers. textbooks, bibliographical sources (each 48%) and primary periodicals (46%) are frequently used sources. Study also shows sericulture scientists not only depend upon their own institute library collection but also a large number of scientists depend upon agricultural libraries (42%) and other sericulture libraries (34%).